Sistem Peminjaman Alat Laboratorium Berbasis RFID dan IoT di Fakultas Kedokteran Gigi UMS - Mulyanto, Hari; Maulindar, Joni; Lestari, Wiji (Fakultas Teknik Universitas Hamzanwadi, 2025)
Laboratories play a crucial role in supporting academic activities at health education institutions. However, inventory management at the Laboratory of the Faculty of Dentistry, Universitas Muhammadiyah Surakarta (UMS), is still conducted manually, leading to recording errors, service delays, and difficulties in real-time equipment monitoring. These issues hinder students from accessing information about the availability and location of equipment needed during practical sessions. This study aims to develop a laboratory equipment loan administration system using Radio Frequency Identification (RFID) technology integrated with the Internet of Things (IoT). The system was developed using the prototyping method, utilizing the ESP8266 and RFID RC522 sensor as the main components to support automated, contactless identification of equipment. The developed system is capable of digitally recording and monitoring the borrowing and returning of equipment in a structured and real-time manner. Testing results show that the system functions properly and meets user needs, although it has a limitation in RFID reading distance, with a maximum range of only 3 cm. This constraint presents a challenge for field implementation. Overall, the system has proven to improve efficiency, accuracy, and transparency in laboratory inventory management and supports the digitalization of technology-based equipment loan processes.